Peningkatan Kadar TNFÎ± Mencit BALB/c dengan Imunosupresi dan Diinfeksi C.albicans Akibat Pemberian Minyak Biji Mimba (Oleum Azadirachty) - Triwahyuni, Iin Eliana (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2011)
Fungal infection in oral cavity is mainly caused by C.albicans and now the case is reported increased. The increasing number of case is parallel with the increasing number of immunosupressed patients. Oleum azadirachty, the active agent of mimba (Azadirachta indica) which is categorized as a herbal medicine that has been used as antifungal drug in agricultural field, and is also found to have immunostimulatory effect in animal model. In addition, TNFÎ± has been known to reduce the spreading of C. albicans and also important for granulocyte antifungal activity. The aim of this research study is to clarify the effect of oleum azadirachty to TNFÎ± level in BALB/c mice cervical lymph node that immunosupressed and infected by C.albicans. This study used BALB/c mice that were devided in to six groups: which is consisted of three groups as control and three groups as studied groups. Mice were immunosupressed by given 2-3mg/mice subcutan injection of prednisolon one day before inoculation. Group 2 until group 6 were given tetracycline hydrochloride in drinking water (0,83mg/ml) since one day before inoculation. C.albicans inoculation was given at zero day. At 2nd day post infection, mice were sacrificed and TNFÎ± level was measured by ELISA. Data were analysed by One Way Anova test and LSD (p=0.05). Result of this research indicated that Oleum Azadirachty could increse the level of TNFÎ±